Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1039/c7cc00865a
|View full text |Cite
|
Sign up to set email alerts
|

A one-pot route to thioamides discovered by gas-phase studies: palladium-mediated CO2 extrusion followed by insertion of isothiocyanates

Abstract: A new palladium mediated "one pot" synthesis of thioamides from aromatic carboxylic acids (ArCOH + RNCS → ArC(S)NHR + CO) was discovered by gas-phase experiments and theoretical studies. Palladium-mediated decarboxylation of aromatic carboxylic acids followed by addition of substituted isothiocyanates leads to the corresponding thioamide derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 28 publications
3
41
2
1
Order By: Relevance
“…3 Both of these modes of reactivity have been widely exploited in the condensed phase to generate organometallic precursors for use in organic synthesis. 4,5 A recent study has used mechanistic insights from MS/MS experiments to develop a new decarboxylative protocol for the synthesis of thioamides, 6 highlighting the value of gas-phase model systems. Here we report on a newly discovered mode of reactivity, ligand-induced decarbonylation (eqn (3)), one that has little precedence in the condensed phase [7][8][9] and is thus of considerable mechanistic interest.…”
mentioning
confidence: 99%
“…3 Both of these modes of reactivity have been widely exploited in the condensed phase to generate organometallic precursors for use in organic synthesis. 4,5 A recent study has used mechanistic insights from MS/MS experiments to develop a new decarboxylative protocol for the synthesis of thioamides, 6 highlighting the value of gas-phase model systems. Here we report on a newly discovered mode of reactivity, ligand-induced decarbonylation (eqn (3)), one that has little precedence in the condensed phase [7][8][9] and is thus of considerable mechanistic interest.…”
mentioning
confidence: 99%
“…The C=S double bond in isothiocyanate compounds has an unsaturated character, and can undergo a Pd‐catalyzed insertion process. (Scheme ) As shown in Figure , when the aryl Pd(II) intermediate 162 is formed, the coordination of an isothiocyanate creates the substitution‐type transition state 164‐ts to form complex 165 . The C=S double bond in the isothiocyanate is inserted into the Pd−C(aryl) bond via the four‐membered ring‐type transition state 166‐ts to form the imidothioate Pd(II) species 167 , which can be further transformed to the thioamide product.…”
Section: Mechanism Of Unsaturated Bond Transformationmentioning
confidence: 99%
“…During studies on the gas‐phase decarboxylation of metal carboxylates and the subsequent reactions of the resultant organometallic ions, 4 it occurred to us that the isoelectronic analogy between CO 2 and heterocumulenes 5 opens the door to developing a new class of reactions for organic synthesis that we have termed ExIn (extrusion–insertion) 6 . In our first study of ExIn reactions, we examined the transformation of a copper(I) coordinated acetate anion into a dithioacetate anion after decarboxylation 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Encouraged by these results, in subsequent studies, we showed that gas‐phase (Scheme 1A) and solution‐phase (Scheme 1B) mechanistic work on 1,10‐phenanthroline (phen) ligated palladium complexes can guide the development of one‐pot synthetic methods for the palladium mediated ExIn synthesis of amides, thioamides, and amidines (Scheme 1C). 6 Given that related phen ligated copper complexes have a long history in decarboxylation reactions 7 and are still being used to develop new decarboxylative coupling reactions, 8 here, we examine the decarboxylation of a suitable model system and the subsequent reactions of the resultant organometallic species with heterocumulenes.…”
Section: Introductionmentioning
confidence: 99%